Feminism and Roles of Women in House of Leaves by Mark Z. Danielewski - Kana vajrayani, Salma; Indra Darmawan, Ruly (LPPM Universitas Advent Indonesia, 2025)
House of Leaves by Mark Z. Danielewski is one of the most prominent example of ergodic literature and post-modern work that utilizes unconventional literary tools. Despite the thorough researchs regarding its metafictional nature and symbolic representations, however, there is still little amount of research that studies the novel from a feminist perspective. This study aims to fulfill that gap by examining the female characters in the novel using feminist theories such as Simone de Beauvoir's Other and Judith Butler's performativity. Findings show that House of Leaves depicts its female characters in contradictory ways, both as passive objects and active agents. In spite of these findings, critical analysis of the deliberation of the female characters' actions is still crucial. These instances becomes an example of how the novel shows a tension between its unconventional nature and gender politics. This study contributes to feminist literary critique by emphasizing the need to examine gender inequality even in experimental novels.